2016
DOI: 10.21307/sjcapp-2016-018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between child maltreatment and exposure to traumatic events during later adolescence and young adulthood

Abstract: Objective: The present study investigated the relationship between different types of childhood maltreatment (emotional abuse, sexual abuse, multiple abuse types, and no abuse) and the occurrence of later traumatic events during later adolescence and young adulthood. Method: Data were collected from a Danish national study conducted by The Danish National Centre for Social Research in 2008 and 2009. A sample of 4718 young adults who were 24 years old was randomly selected using the total birth cohort of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Sexual molestation was a particularly pertinent trauma for this sub-group of participants, with sexual assault and online sexual harassment also heavily endorsed. The high levels of co-occurrence among the sexual trauma events is unsurprising given that sexual-related traumas are highly interrelated with young people exposed to sexual-abuse being particularly vulnerable to subsequent victimizations of a similar nature (Schouwenaars et al, 2016 ; Villalta et al, 2020 ). Likewise, the co-occurrence among the majority of trauma types supports previous research whereby exposure to most forms of victimization or traumatic experiences increases the likelihood that a young person will be exposed to additional traumas (Finkelhor et al, 2007b ).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual molestation was a particularly pertinent trauma for this sub-group of participants, with sexual assault and online sexual harassment also heavily endorsed. The high levels of co-occurrence among the sexual trauma events is unsurprising given that sexual-related traumas are highly interrelated with young people exposed to sexual-abuse being particularly vulnerable to subsequent victimizations of a similar nature (Schouwenaars et al, 2016 ; Villalta et al, 2020 ). Likewise, the co-occurrence among the majority of trauma types supports previous research whereby exposure to most forms of victimization or traumatic experiences increases the likelihood that a young person will be exposed to additional traumas (Finkelhor et al, 2007b ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were presented with a list of lifetime TEs, with good psychometric properties tested in Scandinavian and Baltic populations [ 24 ]. Previous studies have demonstrated that the included events are frequently experienced by youths across nations and cultures and that these events may be traumatizing [ 24 29 ]. These events were related to experiences that occurred during adolescence or early adulthood.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, efforts should be made to consider the overlap and relation between maltreatment and other more general forms of adversity exposure in such higher order or complex models, such as was partially addressed in the bi-factor model created by Lombera et al (2021) with maltreatment and domestic violence. Maltreatment and other types of adversity exposure (e.g., witnessing domestic violence, community violence exposure) tend to co-occur and in some cases may be related to each other (e.g., Schouwenaars et al, 2016). Thus, including all forms of adversity may help provide a more accurate characterization of youths' adversity history.…”
Section: Future Directionsmentioning
confidence: 99%